Effect of simple and radical hysterectomy on quality of life – analysis of all aspects of pelvic floor dysfunction. (March 2016) - Selcuk, Selcuk; Cam, Cetin; Asoglu, Mehmet Resit; Kucukbas, Mehmet; Arinkan, Arzu; Cikman, Muzaffer Seyhan; Karateke, Ates
Abstract: Objective: The impact of simple and radical hysterectomy on all aspects of pelvic floor dysfunctions was evaluated in current study. Study design: This retrospective cohort study included 142 patients; 58 women (40.8%) who have undergone simple, 41 (28.8%) radical hysterectomy, and 43 (30.2%) women without any surgical intervention to serve as the control group. The validated versions of the Urogenital Distress Inventory (UDI-6), Incontinence Impact Questionnaire (IIQ-7), Pelvic Floor and Incontinence Sexual Impact Questionnaire (PISQ-12), Wexner Incontinence Scale score and pelvic organ prolapse quantification (POP-Q) system were used in detailed evaluation of pelvic floor dysfunction. One-way ANOVA and Pearson's chi square tests were performed in statistical analysis. Results: It was found that there were significant differences in irritative and obstructive scores of UDI-6 between Type III hysterectomy group and Type I hysterectomy group. In addition, patients of Type I hysterectomy had significant higher irritative and obstructive scores than the control group. Type III hysterectomy had the most significant deteriorating effect on sexual life, based on scores of PISQ-12 compared to both Type I hysterectomy group and control group. Conclusion: Hysterectomy results in detrimental effects on the quality of life (QoL) regarding all aspects of pelvic floor functions especially in women of radical hysterectomy. Urinary dysfunctional symptoms like urgency, obstruction and especially sexual problems are more bothersome and difficult to overcome. The impact of hysterectomy on QoL should be investigated as a whole and may be more profound than previously thought.